Upaya Meningkatkan Kinerja Guru melalui Kegiatan Supervisi Kelas dalam Proses Pembelajaran pada Satuan Pendidikan SMP - Elya Ratna Hartawati; Saepul Ma'mun; Endi Rochaendi (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
This study aims to gain a thorough understanding of efforts to improve educator performance through classroom supervision in the learning process in junior high schools. The type of research used is classroom action research through Kemmis and Mc. Taggart with four activity stages: planning, action, observation, and reflection. This research began in September 2022 and ended in November 2022. The subjects studied were 17 SMP Negeri and 2 Kiarapedes teachers, consisting of 10 ASN teachers and seven honorary teachers. Data collection utilizes observation and interviews; then, the results are analyzed descriptively and presented as tables and graphs. The study results show that the teacher's performance has increased significantly in the learning process by implementing class supervision activities. This portrait of success is illustrated in the two cycles carried out; initially, in the first cycle, 29.42% of teachers still had less high performance, then in the next cycle, it became 0%. In the first cycle, only 23.53% of teachers had high performance; then, in the second cycle, there was a significant increase to 41.18% of teachers who had quite high performance. In addition, initially, only 47.05% of teachers had high performance (very high and high) in the first cycle and then increased to 58.82% of teachers who had high performance in the second cycle.